Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Loyalitas Pada Karyawan PT. Pitjarus Teknologi Di Jatiasih Bekasi Tahun 2023 - Musriyani Musriyani; Ai Netty Sumidartini (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the effect of Compensation and the Environment work Towards Employee loyalty at PT Pitjarus Teknologi. The sample in this study is Employees at PT Pitjarus Technology. This data collection was carried out by distributing questionnaires with a sample of 50 respondents. The method used in this study uses quantitative methods. This research also uses data analysis techniques such as analysis Descriptive Questionnaire Test, Classical Assumption Test, Multiple Linear Regression Test. Processing in this study uses IBM SPSS version 21. The results of this study are that Compensation and Work Environment have a significant effect on Employee Loyalty At PT Pitjarus Teknologi Employees partially or simultaneously